Novel fluorene-based polyimides with a confined chromophore - Son, SW; Jung, SH; Cho, HN (ELSEVIER SCIENCE SA, 2003)
Novel fluorene-based polyimides with a confined chromophore were synthesized by polycondensation of the fuorene-based dianhydride and the corresponding diamine, followed by partial esterification and imidization. The two precursor polymers, poly(amic acid) and poly(amic ester), were shown to be soluble, stable and highly luminescent, and also easily cast to give nice thin-films. The resulting polyimide obtained by thermal or chemical imidization of poly(amic acid) showed a very weak photoluminescence intensity whereas the poly(amic ester-co-imide) from poly(amic ester) had still strong one.
Keywords: POLYMERS